Correlation and Path Coefficient Analysis of Seed Yield and Yield Components of French Bean (Phaseolus vulgaris L.) Genotypes in Sub-tropical Region - Santosh Kalauni; Deependra Dhakal (Turkish Journal of Agriculture: Food Science and Technology)
This research aims to determine the relationship between yield and yield components of French bean using multivariate statistical techniques. The study was conducted at Horticulture Research Station, Dailekh, Nepal for consecutive three year of 2016-2018. In this study, six French bean genotypes were used. The following measurements and observations were made: germination (%), pod length (cm), pod diameter (mm), individual pod weight and number of seeds pod-1 , number of dry pods plant-1, dry pod yield plant-1 and dry pod yield (t/ha), 100 seed weight (g) and seed yield (t/ha). Highly significant and positive correlation was recorded between seed yield and individual pod weight (r= 0.659***), number of seed pod-1 (r=0.548**) and pod length (0.459*). Conversely, pod diameter showed a negative and non-significant (-0.025) correlation on seed yield. Based on simple regression analysis, linear regression of individual pod weight, number of seed pod-1 and pod length leads to an increase in the seed yield (t/ha) by 0.188, 0.285 and 0.103 units respectively. From the path coefficient analysis maximum positive direct effect on seed yield was recorded by number of seeds pod-1 (0.767) followed by 100 seed weight (0.530) and individual pod weight (0.429). Also, stepwise multiple linear regression analysis revealed that three traits individual pod weight, 100 seed weight and number of dry pod plant-1 account for 68.22% of the total variation in seed yield, while only 31.78% was explained by rest of the variables. Summarizing outcomes of four statistical methods showed that individual pod weight appeared to be the most effective contributor of seed yield followed by the number of seed pod-1, 100 seed weight, and pod length. Therefore, focus should be laid on these characters in future breeding program while selecting genotypes for sub-tropics for improving the seed yield.